A psychological intervention by community pharmacies to prevent depression in adults with subthreshold depression and long-term conditions: the CHEMIST pilot RCT - Elizabeth Littlewood; Carolyn A Chew-Graham; Elizabeth Coleman; Samantha Gascoyne; Claire Sloan; Shehzad Ali; Jay Badenhorst; Della Bailey; Suzanne Crosland; Charlotte EW Kitchen; Dean McMillan; Caroline Pearson; et al. (NIHR Journals Library, 2022)
Background: Depression is common in people with long-term health conditions, and this combination can lead to worsened health outcomes and increased health-care costs. Subthreshold depression, a risk factor for major depression, is prevalent in this population, but many people remain untreated due to the demand on services. The community pharmacy may be an alternative setting to offer mental health support; however, insufficient evidence exists to support implementation. Objectives: To conduct a feasibility study and pilot randomised controlled trial of a community pharmacy-delivered psychological intervention aimed at preventing depression in adults with long-term health conditions. Design: A feasibility study with nested qualitative evaluation and an external pilot, two-arm, 1 : 1 individually randomised controlled trial with nested process and economic evaluations. Setting: Community pharmacies in the north of England. Participants: Adults aged ≥ 18 years with subthreshold depression and at least one long-term health condition. Intervention: A bespoke enhanced support intervention (behavioural activation within a collaborative care framework) involving up to six sessions delivered by trained community pharmacy staff (intervention facilitators) compared with usual care. Main outcome measures: Recruitment and retention rates, completeness of outcome measures and intervention engagement. The intended primary outcome was depression severity at 4 months, assessed by the Patient Health Questionnaire-9. Results: In the feasibility study, 24 participants were recruited. Outcome measure completeness was 95-100%. Retention at 4 months was 83%. Seventeen participants (71%) commenced intervention sessions and all completed two or more sessions. Depression symptoms reduced slightly at 4 months. The process evaluation suggested that the intervention was acceptable to participants and intervention facilitators. In the pilot randomised controlled trial, 44 participants (target of 100 participants) were randomised (intervention, n = 24; usual care, n = 20). Outcome measure completeness was 100%. Retention at 4 months was 93%. Eighteen participants (75%) commenced intervention sessions and 16 completed two or more sessions. Depression symptoms reduced slightly at 4 months, with a slightly larger reduction in the usual-care arm, although the small sample size limits any conclusions. The process evaluation reported good acceptability of the intervention and identified barriers associated with study implementation and its impact on core pharmacy functions. The economic analysis revealed some indication of reduced resource use/costs associated with the intervention, but this is limited by the small sample size. Intervention costs were low. Limitations: The main limitation is the small sample size due to difficulties with recruitment and barriers to implementing the study within existing pharmacy practices. Conclusions: The community pharmacy represents a new setting to deliver a depression prevention intervention. Recruitment was a challenge and pharmacy staff encountered barriers to effective implementation of the study within busy pharmacy practice. Despite these challenges, good retention rates and intervention engagement were demonstrated, and process evaluation suggested that the intervention was acceptable in this setting. To the best of our knowledge, this is the first study to demonstrate that community pharmacy staff can be trained to deliver a depression prevention intervention. Future work: Further work is needed to address barriers to recruitment, intervention delivery and implementation of psychological interventions in the community pharmacy setting. Trial registration: This trial is registered as ISRCTN11290592. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 10, No. 5. See the NIHR Journals Library website for further project information.